2015
DOI: 10.1371/journal.pone.0134445
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of p16/Ki-67 and HPV Test in the Detection of CIN2/3 in Women Diagnosed with ASC-US or LSIL

Abstract: The objective of this study was to compare the accuracies of double staining for p16/Ki-67 and the molecular test for high-risk HPV (hr-HPV) to identify high-grade cervical intraepithelial neoplasia (CIN2/CIN3) in women with cervical cytology of atypical squamous cells of undetermined significance (ASC-US) and low-grade squamous intraepithelial lesion (LSIL). Data were collected from 201 women who underwent cervical cytology screening in the Barretos Cancer Hospital and their results were categorized as ASC-US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 29 publications
(38 reference statements)
6
44
0
2
Order By: Relevance
“…The expression of these markers is associated with the severity of histological lesions. In the Possati-Resende et al study 18 , patients underwent cervical biopsy, ink4a was overexpressed by the immunohistochemical method in more than 50% of the cells of each sample in 43.3% of the cases, presenting a strong intensity in 48.9% of the exams. The Ki67 marker was expressed in 43.6% of the cases (positive in more than 50% of the sample).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The expression of these markers is associated with the severity of histological lesions. In the Possati-Resende et al study 18 , patients underwent cervical biopsy, ink4a was overexpressed by the immunohistochemical method in more than 50% of the cells of each sample in 43.3% of the cases, presenting a strong intensity in 48.9% of the exams. The Ki67 marker was expressed in 43.6% of the cases (positive in more than 50% of the sample).…”
Section: Discussionmentioning
confidence: 94%
“…In our country, however, it is a public health problem.Studies have shown high incidence and mortality in developing countries, andgood control in developed countries whose screening programs are effective 18 . Works have found that the immunohistochemical markers p16 ink4a and Ki67 are more accurate in identifying precursor lesions in patients under 30 years with cervical cytopathological examination compatible with low grade intraepithelial lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Elizabeth Barrios, MSc, (1) Patti Gravitt, PhD, (8) Anna Barbara Moscicki, MD, (9) Kathleen M Schmeler, MD, (10) Yvonne N Flores, PhD, (5,11) Pablo Méndez-Hernández, DSc, (11,12,13) Jorge Salmerón, DSc, (1,5) Torres-Ibarra L y col.…”
Section: Triage Strategies In Cervical Cancer Detection In Mexico: Mementioning
confidence: 99%
“…Together HPV16 and HPV18 along with HPV45 account for 75% of squamous cell carcinoma cases and 94% of adenocarcinomas; 11 b) expression of the oncoprotein E6 as a marker of neoplastic progression; 12 c) cytology for the detection of morphological changes; d) immunocytochemistry for the detection of markers of neoplastic progression like p16INK4a/Ki67, a test with high specificity in the diagnosis of cervical intraepithelial neoplasia of grade 2 or higher (CIN2+). 13,14 The available triage testing alternatives may help identify women who require further diagnostic testing and confirmation, cause less anxiety, and help to avoid unnecessary treatment and expenses in women who have a low risk of progressing to cancer. 1,15,16 In addition, beyond screening and triage, there is no agreement regarding the best method for the diagnostic confirmation of hrHPVpositive women.…”
Section: Triage Strategies In Cervical Cancer Detection In Mexico: Mementioning
confidence: 99%
“…We introduced HPV screening for specific scenarios, as mentioned previously, and the results are very encouraging because the association of a positive hr-HPV test with the immunohistochemical markers p16/Ki-67 identified high-grade cervical intraepithelial neoplasia in women with a cervical cytology of ASCUS and LSIL, revealing 8.4% with HSIL among ASCUS patients, and 22.1% with HSIL among the cytological LSIL group. Separately, we observed that both p16/ Ki-67 double staining and the hr-HPV DNA test had a similar performance in predicting high-grade cervical intraepithelial neoplasia among women with ASCUS [23,24] .…”
Section: Discussionmentioning
confidence: 99%